IMPACT OF PEER ASSISTED GALS LEARNING ON PRECISION IN CLINICAL DIAGNOSIS OF VARIOUS SPINAL DISORDERS - Amit, *Nakanekar; Sharmili, Suryawanshi; Shweta, Telang; Hitesh, Chaudhari; Suraj, Rathod; Jayant, Gulhane (International Journal of Ayurveda and Pharma Research, 2015)
GALS screening examination is a simple, easily reproducible technique which requires minimal clinical instrument. This serves as effective tool in clinical diagnosis and assessment of various disorders. Spine Disorders forms integral part of Outdoor Patient Department (OPD) and Indoor patient department of Ayurvedic hospitals. They also forms integral part of various PG dissertations. Clinical diagnosis of spine disorder is very important. In spite of such enormous burden in OPD & IPD many times Ayurvedic students lack in diagnostic precision of various spinal disorders. Assistance of peer or teacher is very important in learning clinical skill. Aim of present study was to see impact of peer assisted GALS learning on precision in clinical diagnosis and assessment in interns and first year PG students. Total 15 students who were working in unit 3 of Kayachikitsa department were selected for training. 1 months peer assisted GALS skill training was given to them. They were assessed for precision in clinical diagnosis and confidence to diagnose with the help of confidence questionnaire and Final Objective structured clinical examination (OSCE) before and after training along with that open ended response also taken from them about the examination. Data was collected and analyzed based on observations and inference drawn. Peer assisted GALS learning improves clinical performance of students. GALS is a effective clinical tool in clinical diagnosis and assessment of various spinal disorders.